Effect of mineral nutrition and environmental variables on the intensity of wheat spot blotch under rice-wheat system - R.N. SINGH*, V. SINGH and (Indian Phytopathology, 2006)
Experiments were conducted during 2001-02 and 2002-03 to work out the effect of mineral nutrition and environmental variables on the intensity of spot blotch, caused by Cochliobolus sativus (Ito & Kurib.) Drechs. ex Dastur, and grain yield in wheat (Triticum aestivum L. emend. Fiori and Paol.). Mean spot blotch intensity being 38.80% in the first and 38.82% in the second year, environment mediated difference was not apparent at soft dough stage in the timely sown experiment, but at an intensity of 38.19% in the second year over 31.20% in the first, it was very obvious in the late sown one. Environmental variables could not modify the level of spot blotch intensity in timely sown experiment at 120 kg nitrogen, 60 kg phosphorus and 40 kg potash/ha. In the late sown experiment, supplementation of zinc sulphate (21%) and elemental sulphur (32.06%) @ 25 kg/ha each to above NPK dose also gave similar results. Maximum intensity enhancement was noted for 180 kg nitrogen, 60 kg phosphorus and 40 kg potash/ha in the first experiment and zero supplementation of potash, zinc sulphate and elemental sulphur to 120 kg nitrogen and 60 kg phosphorus in the second.